Permanent and Transitory Responses to Capital Gains Taxes: Evidence from a Lifetime Exemption in Canada - Lavecchia, Adam M.; Tazhitdinova, Alisa (The Review of Economics and Statistics, 2026)
Using panel data on a 20% random sample of Canadian taxpayers, we study behavioral responses to the cancellation of a lifetime capital gains exemption that resulted in increased capital gains taxation for some individuals. We show that the exemption did not change the number of taxpayers reporting positive capital gains, and thus unlikely resulted in increased participation in capital markets. Furthermore, our results suggest that the cancellation increased the long-run capital gains realizations of tax filers with more unused exemption room but had a small, statistically insignificant impact on the capital gains realizations of those with little unused exemption room.